Sustainable land management. Challenges, opportunities trade off. - Dutta, Bikram Kumar (My University, 2018)
Land is the integrating component of all livelihoods depending on surface of the earth like: agricultural activity, forest land and water bodies (rivers, lakes, coastal marine) habitats. Due to varying political, social, and economic factors, the heavy use of natural resources to supply a rapidly growing global population and economy has resulted in the unintended mismanagement and degradation of land and ecosystems. In the twenty-first century, the utmost need is to meet three major requirements: (a) adequately supplying safe, nutritious food for the growing population, (b) significantly reducing rural poverty by providing rural household incomes, and (c) reducing and reversing natural resource degradation, especially that of land. India is a developing country and it requires fast space quality infrastructure development, which is the need of current times. For any development, land is required. Accounting land parcel procedure is cumbersome. The assessment of land details are recorded in a system which is more than two hundred years old. The upcoming technologies such as Geographical Information System (GIS), data warehousing and web based information dissemination should be very helpful in land record management for decision making, strategy planning and predictive modelling. The modern web integrates various kinds of advanced, dynamic, multi-layered, time series data and graphical information which transform the tedious data analysis job to a faster, dynamic and realistic exercise. Regular updating of information makes monitoring and management of land parcel in records a more transparent and realistic approach towards any development. This information system can be used as a tool to disseminate information and valuation of land on an open platform. It can also be a useful support system to conserve ecological fragile area. Sustainable Land Management: challenges, opportunities, and trade-offs provides a strategic focus to the implementation of sustainable land management (SLM) components. SLM is a knowledge based procedure that integrates land, water, biodiversity, and environmental management to meet rising food and fiber demands while sustaining livelihoods and the environment. This paper, aimed at policy makers, project managers, and development organisations, articulates priorities for investment in SLM and natural resource management and identifies the policy, institutional and incentive reform options that will accelerate the adoption of SLM productivity improvements and pro-poor growth.
Keywords: Raumordnung; Flächenbedarf; Flächennutzungsplanung; Flächeneinsparung; Nachhaltigkeit; Nachhaltige Raumentwicklung; Flächenmanagement; Bodenmanagement; Bodenpolitik